Students’ Subjective Responses toward Selected Poems in Introduction to Literature Class - Yan Ardian Subhan (Wanastra: Jurnal Bahasa dan Sastra, 2021)
Students’ understanding in form of their responses to literature is important to be researched by educators and researchers. According to Marshall (2000), students response is an indicator of learning’s success. Therefore, this paper discusses students’ subjective responses to literature as result of learning Introduction to Literature subject in one of private universities in Banten, Indonesia. The goal of the research was intended to get insight to students’ subjective responses, to understand their comprehension to selected literary works. The data were taken from essay-test results of their participation in the class. This study is hopefully gaining more understanding of students’ responses to literature..